Alpine gentrification: The mountain village as a metropolitan neighbourhood - Manfred Perlik (Revue de Géographie Alpine)
The article deals with the transformation of mountainous areas into residence places that replace older economic sectors (agriculture, manufacturing and even tourism) in the European mountains from the perspective of regional development and the influence on the regionally anchored assets, known as territorial capital. This new tendency affects the European mountains in two ways and is one element of the constitution of metropolitan regions (metro-regions) that combines metropolitan cores and leisure landscapes as new integral entities. During this process the landscape becomes a new rare commodity and becomes part of the accumulation process of capital. The article states that concepts of landscape aesthetics and amenities cannot explain these new dynamics as they hide spatio-economic processes as well as the role of landscape commodification for the new residents. The new residents are rather multi-locals than migrants. The multi-local character and the selective use of landscape commodities make it difficult to create embeddedness, which is crucial to maintaining and developing territorial capital. It may be assumed that the part-time character of the new residents may rather weaken than strengthen the existing local structures. Therefore it seems necessary to develop specific efforts for each different group of new residents to make from part-time residents (at least part-time) regional actors. Moreover, the concept of regional development based on innovative actors itself has to be questioned as long as consumptive aspects are the prevailing landscape use.